Early corrugated iron construction in South Africa 1820-1920 - Rodd, Harvey Douglas (My University, 2015)
The main purpose of this study was to focus attention on an historically important, but somewhat neglected and overlooked, building material and system o f construction which dominated the urban and suburban scene In South Africa a t the turn of the nineteenth century, namely, corrugated Iron and the so-called wood and Iron form of construction.